Psychological differences and similarities between vegans, prospective vegans, and vegetarians. Motivation, knowledge, vegan literacy – and cheese - Mayrhofer, Roland; Roberts, Lara M.; Hackl, Julia M.; Frischholz, Katja (Frontiers in Psychology, 2024)
Introduction Although vegan and vegetarian diets and lifestyles differ significantly from each other, among other things, notably in their respective consequences regarding animal welfare and their ecological impact, vegans and vegetarians are often grouped together and usually compared to omnivores in psychological research. Considering that vegans and vegetarians often share similar motives for their lifestyle choices, namely animal and environmental issues, the question arises why similar motives lead to different conclusions and correspondingly different behaviors, most notably, of course, that vegetarians consume animal-derived foods such as cheese or milk while vegans do not consume animal-derived products (e.g., food, cosmetic products). This is why this study explored the psychological differences between vegans, vegetarians, and prospective vegans – the latter group being located in an intermediate, transitionary position. Focusing on the motivational, affective and cognitive components of dietary transition and participants’ adherence to eating patterns, reasons for said patterns, possible hinderances to becoming vegan, the role of participants’ social environments, and the impact of various misconceptions regarding the feasibility of a vegan diet in everyday life were all explored. Methods An observational study was conducted via online questionnaire (1420 participants). Results Significant differences were found between vegans, prospective vegans, and vegetarians, especially concerning their knowledge of issues pertaining to their respective lifestyles. Discussion The critical role of knowledge is invoked as an explanation as to why vegans and vegetarians display different behaviors although they share a similar motivation. Thus, in this study the concept of vegan literacy is introduced. Additionally, the distinctive role of cheese is explored, discussing possible indications of its potentially addictive nature and, consequently, the importance of cheese as a hindering factor for pursuing a vegan diet.